O direito dos adolescentes e dos jovens autores de atos infracionais à educação no sistema socioeducativo do Estado do Ceará: desafios e possibilidades para o exercício de uma cidadania fortalecida - Praciano, Marwil Gomes (2018)
The present study analyzes the challenges and possibilities of carrying out the right to education to the adolescents and to the young people in detention under the socio-educational system of the state of Ceará and in compliance with socio-educational measures of detention and semi-liberty detention, especially. This study encompasses the period between the crisis faced by the State System, particularly in the years 2014 and 2015; including the creation of the State Executive Branch, the Superintendency of the State System of Socio-Educational Assistance (Seas) in mid-2016, and the first semesters of its activity and the present time, the beginning of 2018. The chosen period of this analysis illustrates particular changes that have occurred in the treatment of adolescents and of young people in conflict with the law regarding the effectiveness of their right to education. It aims, thus, to demonstrate the evolution of the execution of the public policies related to the realization of the right to education in the form that it occurred previously, as well as in the form concretized by this superintendency, which currently is under the management of the Socio-Educational Centers of Ceará. In addition, it is an attempt to understand how these public policies would be effective, in fact, to provide such adolescents and young people with an ambience so that they become holders of a strengthened citizenship, starting from a process of pedagogical resocialization in the fulfillment of socio-educational measures, according to the Federal Constitution of 1988, the Statute of the Child and Adolescent and the National System of Socio-Educational Assistance prescription. To do so, the methodology addressed in the research is qualitative, bibliographic and normative, with the use and the critical disposition of doctrine and normative diploma on the subject; of quantitative information about the offer of formal education and external activities, such as professionalization, in the Socio-educational Centers of Ceará, for instance; of publications and news published on websites, providing elements for propositions to the problem presented, such as the strengthening of an interinstitutional socio-educational network, the strengthening of other socio-educational measures other than the detention, as well as the insertion of restorative justice practices in this socio-educational system in Ceará.